(untitled) (AYUSHDHARA, 2016)
Kadara has been described as one of the Kshudra roga in Sushruta samhita. It is characterized by hard Granthi type swelling. It amounts to great pain and discomfort when pressure is applied. Even though it is not fatal but makes patient suffer a lot of pain. Patient makes great effort to get rid from this. Kadar can be co-related to corn in modern science. But its management in modern science is not satisfactory. In modern science its treatment includes corn cap application and Surgical excision. Excision of corn is very painful procedure. In modern surgery the only form of treatment of corn that affords any reliable prospect of cure is excision. But the surgeries of corn have an unenviable reputation for subsequent chronic wound healing, more hospitalization etc. Generally is recommended that salicylic acid not to be used by people with diabetes, or when there is frail skin or poor circulation (because of concern about how the skin can heal). Sometime salicylic acid can harmful and allergic to skin moreover by these procedure reoccurrence is very common. So keeping these drawbacks of modern science management, Agnikarma mentioned in Ayurveda selected to give new parameter to management of Kadara. In this present study total 30 patients were selected randomly. They were treated by Agnikarma procedure with Pancloha shalaka in a Systematic manner for duration of 15 days with interval of 5 days in 3 sittings. An excision of Kadar is done by Red Hot Panchloha shalkha. Internally Triphala guggulu 2 tab for 5 days with lukewarm water after food was given. Patient was followed up to 60 days of the procedures to observe and note any reoccurrence. Dressing with Jatyadi Ghrita was done daily in OPD of Shalya tantra department. After completion of clinical trial highly significant result were found in parameter like pain, infection and healing period and no reoccurrence was observed by Agnikarma procedure. By these result it can concluded that Agnikarma is an effective remedy for Kadara.